Pengaruh Kecepatan Kawat Pengumpan Pada Pengelasan GMAW untuk Pengelasan Pipa Air Boiler Baja Karbon Rendah Terhadap Kekuatan Tarik Sambungan Pengelasan di PT.Z - Manahan Hutagalung; Daniel Sirait (CV MEDAN TEKNO SOLUSI, 2025)
This research aims to determine the effect of feed wire speed on the tensile strength of low carbon steel welding results using the GMAW method and also to determine the shape of the welding seam on the tensile strength of the welding joint. In this study, the most suitable test results were obtained from the three test results that had been carried out, namely by using a wire speed of 90 cm/minute with a tensile test result of 0.66 Kgf/mm2. The best seam results are by using a U seam with a tensile strength of 0.71 Kgf/mm2. The benefits of the research can be to find out the appropriate wire speed in the process of welding low carbon steel using the GMAW method and to know the tensile strength of the welded seam shape.